Deteksi Citra Ikan Nila dan Mujair Menggunakan Metode Jaringan Syaraf Tiruan Propagasi Balik - Windharta Oei, Smily; Yahya, Lailany; Wiranto, Ifan (Scimadly Publishing, 2023)
Nile Tilapia and Mozambique Tilapia fish are different, but from the same genus, Oreochromis, these two fish are closely related and have a similar appearance. Therefore, many buyers often find it difficult to distinguish them. This research employs one method in machine learning that is always use to classify image, called Backpropagation in Artificial Neural Network. There were two stages in this study, first was feature extraction using convolution. Second was the learning process using the backpropagation algorithm. Before classification, the image data were prepared by cropping to focus on the classified object. Then from the 254 images, they were divided into three groups, 140 image were for training data, 60 images were for validation data, and 54 were for testing data. The result conluded that the success rate and accuracy reached 74,07% from the total data. To conclude, this method had successfully applied.